Fournier’s gangrene at a tertiary health facility in northwestern Tanzania: a single centre experiences with 84 patients - Chalya, Phillipo L. (BMC Res Notes, 2015)
BACKGROUND: Fournier’s gangrene (FG) is a rare, rapidly progressive, necrotizing fasciitis of the external genitalia and perineum, leading to soft-tissue necrosis. Despite antibiotics and aggressive debridement, the mortality rate of FG remains high. This study describes our experiences in the management of FG and identifies prognostic factors. METHODS: This was a descriptive retrospective study of patients with FG treated at Bugando Medical Centre between November 2006 and April 2014. RESULTS: A total of 84 patients (M:F = 41:1) were studied. The median age was 34 years (range 15–76 years). The most common predisposing factor was diabetes mellitus (16.7 %). Nine (11.3 %) patients were HIV positive. Bacterial culture results were obtained in only 46 (54.8 %) patients. Of these, 38(82.6 %) had polymicrobial bacterial growth while 8 (17.4 %) had monomicrobial bacterial growth. Escherichia coli (28.3 %) were the most frequent bacterial organism isolated. All the microorganisms isolated showed high resistance to commonly used antibiotics except for Meropenem and imipenem, which were 100 % sensitive each respectively. All patients were treated with a common approach of resuscitation, broad-spectrum antibiotics, and wide surgical excision. The median length of hospital stay (LOS) was 28 days and mortality rate was 28.6 %. Systemic inflammatory response syndrome and diabetes mellitus were significantly associated with prolonged LOS (p < 0.001), whereas advancing age (>60 years), late presentation (>48 h), systemic inflammatory response syndrome on admission, diabetes mellitus, extension of infection to the abdominal wall, FG severity score >9 and HIV infection with CD4 count <200 μl/cells) were independent predictors of mortality (p < 0.001). CONCLUSION: Fournier’s gangrene remains a very severe disease with high mortality rates. Early recognition of infection associated with invasive and aggressive treatment is essential for attempting to reduce mortality rates associated with this disease in our setting.